Vigorous physical activity and self-rated health during adolescence: A cross-sectional survey - Wang, Yongkang; She, Weizhong; Chi, Guijun; Wang, Junsheng (Frontiers in Public Health, 2022)
Despite the positive relationship between self-rated health and general physical activity, few types of research touched upon the relationship between self-rated health and vigorous physical activity. It will help promote self-rated health among adolescents by addressing the closest relationship between self-rated health and the components of physical activity. Purpose: In the study, the relationship between self-rated health and vigorous physical activity will be analyzed among Chinese adolescents. Methods: The research will be based on a collaborative survey conducted by WHO in a number of nations, and the data generated by HBSC every four years on health behaviour will be adopted. The samples include typical adolescents aged from 11 to 15 years in China. The school class is taken as a basic unit for sampling. The cluster sampling is performed systematically, and the possibility is proportional to the population. The sampling is conducted to collect typical cases. The class teachers are informed of the sampling activities, and they will collect data on the students by distributing the questionnaires. Results: The research includes 116,828 respondents, and they are from 36 countries. Among them, 51.82% are girls while 48.18% are boys. 98.54% of respondents consider their health status as fair or above when doing the questionnaire, while 1.46% of them believe that their health status is poor. Moreover, 86% and above of respondents participate in vigorous exercise more than weekly, and better results of self-health ratings are found among respondents who exercise more than weekly (Once a week: OR = 1.95, CI: 1.86-2.04; two or three times a week: OR = 1.69, CIL 1.63-1.76; four or six times a week: OR = 1.30, CI: 1.25-1.35). Moreover, it is possible for the respondent to report the better results of self-rated health (4-6 hours every week: OR = 1.36, CI: 1.30-1.43; two or three hours every week: OR = 1.48, CI: 1.42-1.55; 1 hour every week: OR = 1.64, CI: 1.57-1.72). Conclusion: In the study, empirical evidence is provided as to the relationship between self-rated health and vigorous physical activity among adolescents.